Circularly Polarized Omnidirectional Antenna with Dipole Core and Diagonally Adjoined Parasitic Braces for ISM Band Applications - Piyapong Dangkham; Sitthichai Dentri; Chuwong Phongcharoenpanich; Prayoot Akkaraekthalin (My University, 2019)
This research proposes a circularly polarized (CP) single-fed omnidirectional dipole antenna operable in 2.45 GHz frequency for the industrial, scientific, and medical (ISM) radio band applications. The proposed antenna consisted of bisectional dipole core, a pair of quarter-wave baluns, and four diagonally adjoined parasitic braces. The bisectional dipole core was utilized to improve the antenna gain and realize omnidirectional radiation pattern, and the quarter-wave baluns were to symmetrize the current on the bisectional core. The four parasitic braces collectively generated circular polarization. In the study, simulations were conducted using CST Microwave Studio and a prototype antenna fabricated. To validate, experiments were carried out, and simulation and experimental results compared. The finding revealed good agreement between the simulation and experimental results. Essentially, in addition to achieving an antenna gain of 2.07 dBic, the proposed CP single-fed omnidirectional antenna is suited to ISM frequency band applications.
Keywords: Balun; Turnstile antenna; Antenna Design and Analysis